Factors Related to Domestic Violence Court Dispositions in a Large Midwestern Urban Area, 1997-1998: (United States) - Belknap, Joanne ([Verlag nicht ermittelbar], 2001)
The goal of this study was to identify factors that influence whether city misdemeanor domestic violence cases in which batterers are arrested by police result in dismissals, acquittals, or convictions in the courts, and how these cases are processed. The researchers sought to examine factors that influence court officials' decision-making in domestic violence cases, as well as factors that influence victim and witness reluctance in bringing batterers to successful adjudication. In Part 1 researchers merged pretrial services data with information from police and prosecutors' reports in the urban area under study to answer the following questions: (1) What is the rate of dismissals, acquittals, and convictions for misdemeanor court cases and what are the conditions of these sentences? (2) What factors in court cases are significantly related to whether the disposition is a dismissal, acquittal, or conviction, and how are these cases processed? In Part 2, judges, prosecutors, and public defenders were asked detailed questions about their level of knowledge about, attitudes toward, and self-reported behaviors regarding the processing of domestic violence cases to find out: (1) What roles do legal and extra-legal factors play in decision-makers' self-reported behaviors and attitudes? (2) How do decision-makers rate victim advocate and batterer treatment programs? (3) How do court professionals view the victim's role in the court process? and (4) To what degree do court professionals report victim-blaming attitudes and experiences? For Part 3 researchers used a stratified random sample to select court cases of misdemeanor domestic violence that would be transcribed and used for a content analysis to examine: (1) Who speaks in court and how? and (2) What is considered relevant by different court players? In Parts 4-103 victim surveys and interviews were administered to learn about battered women's experiences in both their personal lives and the criminal processing system. Researchers sought to answer the following questions: (1) How do victim/witnesses perceive their role in the prosecution of their abusers? (2) What factors inhibit them from pursuing prosecution? (3) What factors might help them pursue prosecution? and (4) How consistent are the victims'/witnesses' demographic and psychological profiles with existing research in this area? Domestic violence victims attending arraignment between January 1 and December 31 of 1997 were asked to complete surveys to identify their concerns about testifying against their partners and to evaluate the effectiveness of the court system in dealing with domestic violence cases (Part 4). The disposition of each case was subsequently determined by a research team member's examination of defendants' case files and/or court computer files. Upon case closure victims who had both completed a survey and indicated a willingness to be interviewed were contacted to participate in an interview (Parts 5-103). Variables in Part 1, Pretrial Services Data, include prior criminal history, current charges, case disposition, sentence, victim testimony, police testimony, victim's demeanor at trial, judge's conduct, type of abuse involved, weapons used, injuries sustained, and type of evidence available for trial. Demographic variables include age, sex, and race of defendants, victims, prosecutors, and judges. In Part 2, Professional Survey Data, respondents were asked about their tolerance for victims and offenders who appeared in court more than once, actions taken when substance abuse was involved, the importance of injuries in making a decision, attitudes toward battered women, the role of victim advocates and the police, views on restraining orders, and opinion on whether arrest is a deterrent. Demographic variables include age, sex, race, marital status, and years of professional experience. Variables in Part 3, Court Transcript Data, include number and type of charges, pleas, reasons for dismissals, types of evidence submitted by prosecutors and defense, substance abuse by victim and defendant, living arrangements and number of children of victim and defendant, specific type of abuse, injuries sustained, witnesses to injuries, police testimony, verdict, and sentence. Demographic variables include age and sex of defendant and victim and relationship of victim and defendant. In Part 4, Victim Survey Data, victims were asked about their relationship and living arrangements with the defendant, concerns about testifying in court, desired outcomes of case and punishment for defendant, emotional issues related to abuse, health problems, substance abuse, support networks, other violent domestic incidents and injuries, and safety concerns. Part 5 variables measured victims' safety at different stages of the criminal justice process and danger experienced due to further violent incidents, presence of weapons, and threats of homicide or suicide. Parts 6-103 contain the qualitative interview data.